Multiplexed probing of proteolytic enzymes using mass cytometry-compatible activity-based probes. - Poreba, Marcin (J Am Chem Soc, 2020)
The subset of the proteome that contains enzymes in their catalytically active form can be interrogated by using probes targeted towards individual specific enzymes. A subset of such enzymes are proteases that are frequently studied with activity-based probes, small inhibitors equipped with a detectable tag, commonly a fluorophore. Due to the spectral overlap of these commonly used fluorophores, multiplex analysis becomes limited. To overcome this, we developed a series of protease-selective lanthanide-labeled probes compatible with mass cytometry giving us the ability to monitor the activity of multiple proteases in parallel. Using these probes we were able to identify the distribution of four proteases with different active site geometries in three cell lines and peripheral blood mononuclear cells. This provides a framework for the use of mass cytometry for multiplexed enzyme activity detection.